1989
DOI: 10.5951/jresematheduc.20.3.0274
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Syntax of Algebra

Abstract: A structured system of visual features can be seen to parallel the propositional hierarchy of operations usually associated with the parsing of algebraic expressions. Some students (proportionately more women than men) were found to depend on these visual cues in their syntactic decision making. Others were found to have access to sound propositional rules. Possible causes and consequences of these different syntactic representation styles are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
2
20
0
3
Order By: Relevance
“…Here, formal structure is mirrored in the visual grouping structure created both by the spacing ( b and c are multiplied, then added to a ) and by the physical demarcation of the horizontal line. Instead of applying abstract mathematical rules to process such expressions, Landy and Goldstone ( 2007a , b see also Kirshner, 1989 ) propose that reasoners leverage visual grouping strategies to directly segment such equations into multi-symbol visual chunks. To test this hypothesis, they investigated the way manipulations of visual groups affect participants' application of operator precedence rules.…”
Section: Perceptual Manipulations Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, formal structure is mirrored in the visual grouping structure created both by the spacing ( b and c are multiplied, then added to a ) and by the physical demarcation of the horizontal line. Instead of applying abstract mathematical rules to process such expressions, Landy and Goldstone ( 2007a , b see also Kirshner, 1989 ) propose that reasoners leverage visual grouping strategies to directly segment such equations into multi-symbol visual chunks. To test this hypothesis, they investigated the way manipulations of visual groups affect participants' application of operator precedence rules.…”
Section: Perceptual Manipulations Theorymentioning
confidence: 99%
“…Nor is this pattern restricted to algebraic validity. Related research has indicated that spatial layout impacts application of the order of operations rules when calculating (Kirshner, 1989 ; Landy and Goldstone, 2010 ), when creating story problems (Jiang et al, in press ), and when working in programming languages such as Python (Hansen et al, unpublished manuscript ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several authors have reported that algebraic reasoning co-opts mechanisms involved in perception and manipulation of physical objects (Dörfler 2004; Kirshner 1989; Landy & Goldstone 2007; Landy & Goldstone 2008). For example, Landy and Goldstone (2007) report that reasoners systematically utilize processes of perceptual grouping to proxy for the ordering of algebraic operations.…”
mentioning
confidence: 93%
“…Öğrencilerin temsiller arası dönüşümleri başarılı bir şekilde gerçekleştirmek için, değişkenleri ve sözel durumlarda yer alan değişkenler arasındaki ilişkiyi, bunun yanında sembolik temsil sisteminin söz-dizimsel özelliklerini anlamaları gerekmektedir (Kaput, 1989). Öğrencilerin cebirsel bir ifadenin söz-dizimsel yapısını anlama becerisinin cebirde başarılı olmak için temel olduğu ileri sürülmektedir (Kirshner, 1989).…”
Section: Introductionunclassified
“…Bir başka araştırmada, farklı türlerde sunulan problemlerde öğrencilerin zorlandıkları noktalar incelenmiş ve öğrencilerin sözel bağlamlar ile sunulan problemlerde sembolik bağlamlar ile sunulan problemlere oranla daha başarılı oldukları ve öğrencilerin sembolik ifadeleri okumak konusunda daha başarısız oldukları ortaya çıkmıştır (Koedinger ve Nathan, 2004). Bunun yanında sözel ve sembolik temsil araştırmalarında, öğrencilerin bu temsiller arasındaki dönüşümleri gerçekleştirmeleri için gereken temel becerilerin belirlenmesine yönelik incelemelerde bulunmuşlardır (Kirshner, 1989). Alan yazındaki bu araştırma sonuçlarının sentezinin ardından, bir sonraki bölümde bu araştırmayı destekleyen kavramsal çerçeve açıklanacaktır.…”
Section: Introductionunclassified